Highly Purified Lipoteichoic Acid from Staphylococcus aureus Induces Procoagulant Activity and Tissue Factor Expression in Human Monocytes but Is a Weak Inducer in Whole Blood: Comparison with Peptidoglycan - Mattsson, Eva (American Society for Microbiology, 2004)
Lipoteichoic acid from Staphylococcus aureus was a potent inducer of procoagulant activity in isolated mononuclear cells but not in whole blood. In contrast, staphylococcal peptidoglycan showed equal levels of potency in isolated mononuclear cells and whole blood, suggesting that peptidoglycan is an important inducer of procoagulant activity in severe sepsis involving gram-positive bacteria.